2014
DOI: 10.1007/s00216-014-8340-4
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol-sulfates: identification and quantification of novel conjugated (masked) mycotoxins in wheat

Abstract: We report the identification of deoxynivalenol-3-sulfate and deoxynivalenol-15-sulfate as two novel metabolites of the trichothecene mycotoxin deoxynivalenol in wheat. Wheat ears which were either artificially infected with Fusarium graminearum or directly treated with the major Fusarium toxin deoxynivalenol (DON) were sampled 96 h after treatment. Reference standards, which have been chemically synthesized and confirmed by NMR, were used to establish a liquid chromatography-electrospray ionization (LC-ESI)-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 23 publications
0
61
1
2
Order By: Relevance
“…The details about the endogenous self-protection mechanism against DON in Trichoderma strains needs further investigation and interpretation after the detoxification UGT genes from Trichoderma are identified. On the other hand, other detoxification products of DON have been identified in plant detoxification processes, such as DON-sulfates, DON-15-glucoside, and DON-glutathione [25,40,41]. Seeking and identifying other modified mycotoxins generated from Trichoderma and Fusarium are also essential to reveal the mycotoxin detoxification mechanism of Trichoderma .…”
Section: Discussionmentioning
confidence: 99%
“…The details about the endogenous self-protection mechanism against DON in Trichoderma strains needs further investigation and interpretation after the detoxification UGT genes from Trichoderma are identified. On the other hand, other detoxification products of DON have been identified in plant detoxification processes, such as DON-sulfates, DON-15-glucoside, and DON-glutathione [25,40,41]. Seeking and identifying other modified mycotoxins generated from Trichoderma and Fusarium are also essential to reveal the mycotoxin detoxification mechanism of Trichoderma .…”
Section: Discussionmentioning
confidence: 99%
“…Several conjugated forms of DON such as DON-3-glucoside (Poppenberger et al 2003) and DON sulfates (Warth et al 2015), but also of zearalenone and fumonisins have been identified to date (De Saeger and Van Egmond 2012;Berthiller et al 2013).…”
Section: The Masked Mycotoxin Problemmentioning
confidence: 99%
“…Several DON derivatives have been identified as DON-sulfonates, 4,5 DONsulfates, 6 or DON−glutathione conjugates. 3,7 Glutathione (GSH) is a natural tripeptide containing cysteine and possesses a free thiol (−SH) group that behaves both as a nucleophile and as a reducing agent.…”
Section: ■ Introductionmentioning
confidence: 99%